Biotechnology of functional proteins and peptides for hair cosmetic formulations - Tinoco, Ana (2022)
Cosmetics procedures and products combined with environmental insults and daily routines induce irreversible changes in hair. As result of damage, the hair loses some of its properties like strength, elasticity, and smoothness. Recent studies revealed the positive effects of protein-based cosmetics in providing protection to hair. Additionally, these cosmetic products have also shown a great ability to modify hair fibers. We review the effect of protein-based cosmetic formulations on hair properties like color, scent, strength, shape, and volume, highlighting the potential of keratin-based particles and keratin-fusion proteins. In the future, incorporating multifunctional proteins and peptides in the development of alternative hair formulations will result in advanced, sustainable, ecofriendly cosmetic products with a great impact on the cosmetic industry.